Analysis of jokes technique in TikTok contents as English learning media - Erika Sinambela; Bimbi Izumi Sembiring; Sondang Manik; Darman Pangaribuan (Inovasi Kurikulum, 2024)
English is a foreign language studied in schools and is one of the compulsory subjects. However, a problem occurs in its implementation: the tendency to learn English using a focused memorization method. This can hinder English learning, focusing on the concept that language is part of culture, not just a series of memorized words. One learning method that can be used is by implementing humor. Humor serves as a bridge between teachers and students to create a more relaxed and comfortable classroom environment. This research aims to investigate the source of English Learning materials in the form of jokes from Stand-Up Comedians and ensure their use in English learning routines. The approach used in this research is descriptive qualitative, using the observation method. The research sample consists of 25 videos containing jokes obtained from English Stand-Up Comedians' TikTok user accounts. The data was then analyzed to identify the types of jokes used in each video and their use in English learning. The results show that the type of joke widely used in the content is Ridicule; however, the suitable joke techniques for use in English learning in the classroom are Politeness Strategy and Paralanguage.